Effect of monoethanolamine concentration on CO2 capture by poly (chloromethyl styrene) grafted fibrous adsorbent - Mohamad, N.A. (Institute of Physics Publishing, 2020)
The CO2 adsorption performance of poly (chloromethyl styrene) (PCMS) grafted on polyethylene coated polypropylene (PE/PP) fibrous polymer substrate and followed by amination with monoethanolamine (MEA) was investigated using gravimetric sorption system. The chemical, structural and morphological changes in the aminated adsorbents were evaluated using Fourier transform infrared spectroscopy (FTIR) and X-ray diffraction (XRD), respectively. The amination was carried out using three different compositions of MEA (50, 80 and 100) diluted in water to optimize the yield of loaded amine. The highest percent of amination obtained was about 71 and the amine content increase with the rise in MEA concentration. The CO2 adsorption capacity increase with MEA concentration with the highest capacity recorded was1.63 mmol/g with pure CO2 gas at 30 bars and room temperature. Â© Published under licence by IOP Publishing Ltd.